2002
DOI: 10.1289/ehp.02110125
|View full text |Cite
|
Sign up to set email alerts
|

Dichlorodiphenyltrichloroethane (DDT): ubiquity, persistence, and risks.

Abstract: Due to uncontrolled use for several decades, dichlorodiphenyltrichloroethane (DDT), probably the best known and most useful insecticide in the world, has damaged wildlife and might have negative effects on human health. This review gives a brief history of the use of DDT in various countries and presents the results of epidemiologic and experimental studies of carcinogenesis. Even though its use has been prohibited in most countries for ecologic considerations, mainly because of its negative impact on wildlife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
244
0
8

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 548 publications
(255 citation statements)
references
References 55 publications
3
244
0
8
Order By: Relevance
“…It is hypothesized that they can cause adverse effects by interfering in some way with the bodyÕs hormones or chemical messengers and may induce a broad spectrum of biochemical and toxic responses at low environmentally relevant dose . Their potential health effects include reproductive disorders, cancer and impaired development (Hileman, 1994;Colborn and Smolen, 1996;Turusov et al, 2002;Zhou et al, 2004). Studies have suggested that some pesticides have been identified as potential or suspected endocrine disruptors.…”
Section: Introductionmentioning
confidence: 99%
“…It is hypothesized that they can cause adverse effects by interfering in some way with the bodyÕs hormones or chemical messengers and may induce a broad spectrum of biochemical and toxic responses at low environmentally relevant dose . Their potential health effects include reproductive disorders, cancer and impaired development (Hileman, 1994;Colborn and Smolen, 1996;Turusov et al, 2002;Zhou et al, 2004). Studies have suggested that some pesticides have been identified as potential or suspected endocrine disruptors.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the potential health effects of endocrine disrupters including reproductive disorders, cancer, and impaired development (Hileman 1994;Colborn and Smolen 1996;Turusov et al 2002;Zhou et al 2004), trace endocrine-disrupting pesticides in the water body have attracted extensive interest from environmental scientists and the public. Studies have suggested that some pesticides have been identified as potential or suspected endocrine disrupters (Kelce et al 1995;Zhan et al 2000;Ren and Jiang 2001;Hemmer et al 2001).…”
mentioning
confidence: 99%
“…In the former, tests in oophorectomized rats or those with low-weight uteruses showed an important response to the metabolite o,p'-DDT, inhibiting estradiol binding to uterine receptors. In the latter, some DDT and DDE metabolites proved capable of inducing MCF-7 cell proliferation in breast tumors, which are estrogendependent 44 .…”
Section: Post-natalmentioning
confidence: 99%
“…Turusov et al 44 report the estrogen-like potential of DDT, assessed in vivo and in vitro. In the former, tests in oophorectomized rats or those with low-weight uteruses showed an important response to the metabolite o,p'-DDT, inhibiting estradiol binding to uterine receptors.…”
Section: Post-natalmentioning
confidence: 99%